OTORITAS JASA KEUANGAN (OJK) SEBAGAI PENGAWAS LEMBAGA KEUANGAN DAN NON KEUANGAN YANG INDEPENDEN DI INDONESIA - Utami, Yuni; ., Tabrani (PERMANA, 2012)
Financial Services Authority (FSA)orFinancial ServicesInstitutionsdefined asinstitutions thatcarry outactivitiesin thesectors ofBanking, Capital Markets, Insurance, Pension Funds, Banking Institutions, andOther FinancialServicesAgency. Theseinstitutionsareindependentand freefrom the interferenceof others,which havethe functions, duties, andauthorityregulation, supervision, inspectionandinvestigation. FinancialServices Authoritywas formed in ordertocope withthe complexityofthe threat ofglobalfinancialcrisis,eliminatingabuse of power, and thesearch forefficiencyin bankingandother financial institutions.Financial servicesauthorityestablishedwith the aim thatthe overallactivityinthefinancial servicessector: heldon a regular basis, fair, transparent and accountablefinancialsystemable to realizea sustainable andstablegrowth, and able to protectthe interests ofconsumersandsociety. Authoritiesimplement thefunctionof financial servicesregulation and supervisionare integratedto the overallactivityinthefinancial services sector. Becausein practicelater on, especially forthe bankingindustry, financial servicesauthoritywillperform someimportanttasksfor the regulationandsupervision ofbankingsector(microprudential), which includesinstitutionalbank, bankhealth, prudentialaspectsof banks andbankchecks. Withsome tasks, it still takesan experiencedprofessional staffmust be supportedbytheHuman Resourcessystemandreliable, which is no doubt.